2021
DOI: 10.1039/d0ce01128b
|View full text |Cite
|
Sign up to set email alerts
|

The crystal growth of ortho- and pyrosilicates from W and Mo crucibles

Abstract: The feasibility to grow bulk La-GPS:Ce scintillation crystals by the Czochralski method using Mo crucibles has been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
4
5
0
Order By: Relevance
“…The absolute light yield of sample 3 reached 24100 ph./MeV with an energy resolution of 10 % (Table 2). This value remarkably lower than the best values of the light yield described in the literature [32] but coincided with that presented in our previous work [11]. On the other hand, energy resolution almost doubled in comparison to [11], which indicates the improved quality of the crystals obtained in this work.…”
Section: Scintillation Propertiessupporting
confidence: 88%
See 3 more Smart Citations
“…The absolute light yield of sample 3 reached 24100 ph./MeV with an energy resolution of 10 % (Table 2). This value remarkably lower than the best values of the light yield described in the literature [32] but coincided with that presented in our previous work [11]. On the other hand, energy resolution almost doubled in comparison to [11], which indicates the improved quality of the crystals obtained in this work.…”
Section: Scintillation Propertiessupporting
confidence: 88%
“…In our case, there are no structured Ce 3+ peaks due to a relatively large Ce 3+ concentration and a very high optical density of Ce 3+ in this range, just wide bands in the 270-350 nm and <250 nm both at absorption and excitation spectra. The same spectral shape was observed in many earlier studies, see, for example [11,31]. The photoluminescence spectrum (Figure 3b) contains a typical luminescence bands peaked at 367 nm and 390 nm associated with the transition to 2 F5/2 and 2 F7/2 terms of the split ground state of Ce 3+ ions [29] excited in the UV-band.…”
Section: Optical Propertiessupporting
confidence: 81%
See 2 more Smart Citations
“…Nowadays, the price of Ir has even increased several times with no trace of a trend reversal in sight. This is reflected in the higher interest for Mo and W crucible technologies in the community. It was shown that, in general, the ions constituting a crucible material can penetrate into the crystal. , In some cases (e.g., when using the Mo crucible), it can even improve the scintillation characteristics . In the case of GAGG, the effect of codoping of CZ-grown single crystals by W and Mo had been recently studied and was found to be rather complex.…”
Section: Introductionmentioning
confidence: 99%